Intensity Calibration and Flat‐Field Correction for Fluorescence Microscopes. Issue 1 (1st April 2014) - Model, Michael
Abstract: Standardization in fluorescence microscopy involves calibration of intensity in reproducible units and correction for spatial nonuniformity of illumination (flat‐field or shading correction). Both goals can be achieved using concentrated solutions of fluorescent dyes. When a drop of a highly concentrated fluorescent dye is placed between a slide and a coverslip it produces a spatially uniform field, resistant to photobleaching and with reproducible quantum yield; it can be used as a brightness standard for wide‐field and confocal microscopes. For wide‐field microscopes, calibration can be further extended to absolute molecular units. This can be done by imaging a solution of known concentration and known depth; the latter can be prepared by placing a small spherical lens in a diluted solution of the same fluorophore that is used in the biological specimen. Curr. Protoc. Cytom . 68:10.14.1‐10.14.10. © 2014 by John Wiley & Sons, Inc.